Research an Investigation into Mixed Media Painting Learning in the Context of University Art Education - Wang Ke; Mohammad Puad Bin Bebit; Lilian Lee Shiau Gee (Eurasian Journal of Educational Research, 2022)
Purpose: This study aims to investigate how Chinese university students learn in mixed media painting courses and assess their comprehension of the significance of material categories, subject matter, and artistic expression techniques. Methodology： Using a quantitative research methodology, non-random judgmental sampling was conducted. Six universities from diverse regions of China were selected, and a questionnaire based on the Likert scale was developed. Using SPSSAU, the dependability of the items and architectures and the connections between the structures were evaluated. Results: Initially, the students' enthusiasm for mixed-media paintings vastly outweighed their knowledge. Some pupils' conceptual comprehension, material selection, and expressive style still require clarification, which must be addressed. Implications: This thesis comprehensively examines and analyzes student learning in mixed media painting courses within university art education to broaden research perspectives and ideas in related fields. It stimulates the development of art education in Chinese colleges and universities. Due to the accelerated development of China's economy and culture, the advancement of art education in colleges and universities has become increasingly crucial. This dissertation comprehensively examines and investigates students' learning in mixed media programs. The research presented in this thesis will promote the development of mixed-media painting education in China and enhance the learning levels of university students.